Shibotik: Inovasi Kreatif Teknik Pewarnaan Kain Batik (Studi Kasus Industri Kerajinan Batik Komar) - Dipodiwiryo, Rafi Arlei (PT. Banjarese Pacific Indonesia, 2023)
This research aims to explore innovation in batik coloring techniques through the collaboration of conventional wax and stamp methods with Shibori resist dyeing, known as Shibotik. Conducted at Batik Komar, the qualitative approach employed involved participant observation and in-depth interviews. Over a five-month period, the researcher actively engaged in activities at the batik house, observing production processes, interacting with craftsmen, and creating works using Shibotik coloring techniques. The findings reveal that Batik Komar successfully developed Shibotik as an innovative form of textile art. By combining six basic Shibori dyeing techniques—Arashi, Itajime, Kanoko, Kumo, Miura, and Nui—they created new patterns that blend the clarity of traditional batik motifs with the unpredictable edges of Shibori motifs. This collaboration not only produces beautiful and narrative fabrics but also has a positive impact on the community. The increased interest in Shibori, particularly among young entrepreneurs, creates economic opportunities and new jobs. However, suggestions for further research highlight the creative potential of coloring techniques and their economic and cultural impact, particularly on Indonesia's cultural heritage. The study also outlines practical implications, such as enhancing education and training opportunities in batik and Shibori techniques at the local level. Additionally, the emphasis on sustainability suggests investigating the application of Shibori techniques with environmentally friendly principles. In conclusion, Shibotik contributes not only to preserving Indonesia's batik heritage but also opens new potentials in the creative industry. Its novelty lies in cross-cultural collaboration and the creative utilization of coloring techniques, presenting new opportunities for textile art development. The implications can guide further research in the contexts of education and the sustainability of traditional arts.